2012
DOI: 10.1093/aje/kwr373
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Human Papillomavirus Seropositivity and Risk of Nonmelanoma Skin Cancer

Abstract: Cutaneous human papillomaviruses (HPVs) have been associated with squamous cell carcinoma (SCC) in case-control studies, but there are limited data from prospective studies assessing whether virus exposure predicts risk of future cancer development. Two major biobanks, the Southern Sweden Microbiology Biobank (1971-2003) and the Janus Biobank (1973-2003) in Norway, containing samples from 850,000 donors, were searched for incident skin cancer for up to 30 years using registry linkages. Altogether, 2,623 donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 29 publications
9
63
3
1
Order By: Relevance
“…Case‐control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5‐ to 3‐fold increased risk of cSCC 12, 20, 21, 22, 23, 24, 25, 26, 29, 31, 32. It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV.…”
Section: Introductionmentioning
confidence: 99%
“…Case‐control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5‐ to 3‐fold increased risk of cSCC 12, 20, 21, 22, 23, 24, 25, 26, 29, 31, 32. It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported weak associations between HPV types 3, 15, 38, and 76 and future risk of SCC (3). The previous study was carried out using an HPV serologic method (GST-L1 fusion proteins) that has only weak association with HPV infection (4).…”
Section: Introductionmentioning
confidence: 93%
“…The samples from cases and matched controls were tested for IgG to pseudovirions to 16 different HPV types (3,5,6, 11, 15, 16, 18, 31, 32, 33, 38, 45, 52, 58, 68, and 76) and two polyomaviruses (MCPyV and JCPyV).…”
Section: Introductionmentioning
confidence: 99%
“…Out of 45 studies reported during 1991 to 2017; two studies were reported in Australia [12,13], one Romania [14], ten USA [15,16,17,18,19,20,21,22,23,24], one Argentina [1], four Netherlands [25,26,27,28], two Spain [8,11], one Brazil [29], one China [30], one UK [31], one Croatia [2], four Iran [9,32,33,34], one North Africa/France [35], one Germany/USA [36], two Greece [37,38], one Sweden/Austria [39], two Germany [40,41], five Italy [5,42,43,44,45], one Russia [46], one Germany/Poland [47], one Norway/Sweden [48] and two Sweden [49,50] (Table I). Fifteen studies were case-control and 30 studies were cross-sectional studies.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%